KEMATANGAN KARIR REMAJA DALAM PERSPEKTIF ISLAM - Agam Anantama (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
Teenage career maturity is a major problem that occurs in the world of Indonesian education today. Various theories and disciplines have been studied to prepare teenagers to have career maturity. Understanding career maturity is not only reviewed in General Science disciplines such as Psychology, because since a long time Islam has discussed a lot about the personality and maturity of adolescents that can be used as a basis in understanding career maturity in an Islamic perspective. . As much as the amount of human knowledge gained through reason cannot be separated from the heart so that there tends to be a potential for indifference in seeing psychological theories about humans that can cause fatal errors in implementing it. In the context of career maturity, individuals who choose jobs are based on satisfaction, often unresolved problem. All kinds of careers cannot be separated from Islamic values ​​because all jobs, careers, positions are intended to serve and seek God's pleasure.